Go Ahead, Secret Seven - "Blyton, Enid" (Hodder Children's Books: London, 2002)
An enduringly popular series, now with fun new covers! George is in trouble and has to resign from the Secret Seven - now it's up to Scamper the spaniel to protect the rest of the gang from danger as the go in search of some missing pedigree dogs ...
Keywords: Mystery fiction